American Youth Violence. - Zimring, Franklin E. (Studies in crime and public policy., 1998)
This is the definitive examination of adolescent violence in the United States as both a social phenomenon and a policy problem. Franklin Zimring, one of America's most esteemed scholars of law and crime, scrutinized criminal statistics and demographic trends. The result is a thorough debunking of Congressional predictions of ""a coming storm of juvenile violence"" and the half-baked policy proposals that accompany such warnings. The book sets forth comprehensive and dispassionate analyses of three key areas of youth violence policy: adolescent firearms possession and use, standards for transf.